Self-Management Integrated with Health Belief-Based Education on Blood Pressure and Quality of Life in Uncontrolled Hypertension: A Quasi-Experimental Study - Tata Mahyuvi; Mohammad Fanani; Indasah Indasah; Joko Prasetyo; Délia Moreira Amaral do Rosário (Jurnal Keperawatan Soedirman, 2026)
Self-management and the Health Belief Model (HBM) have been shown to improve blood pressure control and quality of life (QoL). However, the effectiveness of integration self-management with HBM for hypertension requires further clarification. This study examined the effect of integration self-management with HBM on blood pressure and QoL among individuals with uncontrolled hypertension. A total of 138 eligible participants were allocated into two groups: one receiving self-management integrated with HBM-based education (n = 69) and the other receiving regular education (n = 69). Independent t-tests, Chi-squared tests, and generalized estimating equation (GEE) were conducted. The findings showed a significant interaction between groups in systolic blood pressure (SBP) and diastolic blood pressure (DBP) after 12 weeks compared to the control group (p < 0.001). Importantly, there was a significant increase in QoL across physical, psychological, social relationships, and environmental domains. Specifically, the intervention group demonstrated significantly higher QoL scores than the control group over time (β = 22.756, 95% CI [20.623, 24.901], p < 0.001). The effectiveness of integration self-management with HBM significantly reduced blood pressure and increased QoL.